KNOWLEDGE AND ATTITUDES OF PROSPECTIVE BRIDES AND GROOMS TOWARDS PREMARITAL SCREENING BEHAVIOR AT KUA PURWASARI KARAWANG DISTRICT IN 2023 - Nency, Olivia; Sriwahyuni, Erna (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: In other countries, premarital screening has become a mandatory requirement for couples who are getting married. This is because not everyone has a good health history. A person who appears healthy may be a carrier of the disease. Writing purpose: To find out the knowledge and attitudes of prospective brides and grooms towards premarital screening behavior at the KUA Purwasari Karawang District in 2023. Research Method: This research uses a quantitative type of research using a descriptive design with a cross-sectional study approach. The sample in this study amounted to 105 people, chi-square statistical analysis test. Research Results: There is an influence of knowledge (p value=0.009) and attitude (p value=0.001) on premarital screening behavior. The dominant factor that has the most influence is attitude with a p-value = 0.001 and an exp (B) value of 3.843. Conclusions and Suggestions: It is hoped that prospective brides and grooms can increase their knowledge by actively seeking information about wedding preparations, especially health problems and diseases that can be inherited so that awareness of the importance of premarital screening arises which is useful for preventing and overcoming health problems in the future.